Demonstration of the double Penning trap technique with a single proton - Mooser, Andreas; Bräuninger, S.; Franke, Karsten; Kracke, Holger; Leiteritz, C.; Rodegheri, Crícia de Carvalho; Nagahama, H.; Schneider, G.; Smorra, C.; Blaum, Klaus; Matsuda, Y.; Quint, Wolfgang; et al. (Physics letters, 2013)
Spin flips of a single proton were driven in a Penning trap with a homogeneous magnetic field. For the spin-state analysis the proton was transported into a second Penning trap with a superimposed magnetic bottle, and the continuous Stern-Gerlach effect was applied. This first demonstration of the double Penning trap technique with a single proton suggests that the antiproton magnetic moment measurement can potentially be improved by three orders of magnitude or more.